Readiness of Road Project Contractors to Use Musharakah: Evidence from Jakarta (Qualitative Study) - Buana, Mohamad Torik Langlang; Dali, Nuradli Ridzwan Shah Mohd; Amrizal, Amrizal; Saratian, Eko Tama Putra (AL-MUZARA'AH, 2025)
The Islamic banking industry in Indonesia has received full support from the government, manifested in comprehensive policies, e.g., Islamic Banking Roadmap, Islamic Finance Architecture and other programs. The government is also focusing on infrastructure development, including roads. The success of this program is determined mainly by construction services companies or contractors. During the last 10 years, on average there have been more than 200,000 contractors in Indonesia. Musharakah is suitable for construction companies because its characteristics are similar to their work model, namely cooperation. This study aims to determine the readiness of contractors to use musharakah financing. It employed the qualitative method. The sample was private infrastructure contractors in Jakarta working on national road projects. Data was collected through interviews. The study revealed that many private contractors were not familiar with musharakah financing because of their low awareness of Islamic banks. The study suggests that Islamic banks should make initiatives to serve the corporate segment. By combining information from different entities, the results offer valuable insights into how the contractors are a potential segment for Islamic banks, a segment that is currently the government's priority.